Good Inspiring The Strength of Enterpreneurship Character - Balok, Servasius (Indonesian Character Journal, 2024)
The inspiration for the strength of entrepreneurial character is the breath or encouragement to continue to think creatively from someone in creating something new and different. Inspiration for entrepreneurial character can occur within the framework of cultural interactions that flow naturally and informally with people's lives. This research aims to map the inspiration of entrepreneurial power and analyze the factors that underlie the process of cultural interaction. The research was designed in a qualitative design with data collection methods in the form of observation, in-depth interviews. Data analysis was carried out by manual reduction, display and interpretation of data. The results of the study show that inspiration runs in the entrepreneurial process which is characterized by the strength of social interaction that is increasingly attractive and gives interest so that the business is progressing and growing every year. The inspiration for the power of entrepreneurship cannot be separated from the role of cultural interaction presented by the entrepreneur personally, both formally and informally. The limitation of this study is that the scope of the study is limited to one community group. It is possible to find comparisons by studying in a wider space.